Nursing Care of Patients with Multiple Sclerosis During Immunomodulatory Treatment of First-line Drugs - Maria Wilkiewicz; Anna Smelkowska; Krystyna Jaracz; Barbara Grabowska-Fudala; Joanna Pniewska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Multiple Sclerosis (SM) is a chronic demyelinating disease of the central nervoussystem with immunological background. MS is most frequently diagnosed in people between 20 and 40 years of age, and this isinmost cases the relapsing — remitting form of the disease. Immunomodulatory therapy used in these patients isto reduce the frequency of relapses, thus the inhibition of progressive neurological disability and improvement of quality of life of patients is reached. At present in Poland the registered drugs in the treatment of immunomodulatory relapsing — remitting form of multiple sclerosis include: interferons, glatiramer acetate, natalizumabifingolimod. The condition for the effectiveness of this therapy is to follow the rules of procedure by the patient during the entire treatment period. The role of nurses in this area is very important. This paper presents the role of nurses in the course of immunomodulatory therapy of first-line drugs. These drugs include interferons and glatiramer acetate. Since the start of therapy by the patient, the nurse takes an active part in educating, monitoring, and providing support to the patient during the entire treatment period. Nursing interventions in these areas are varied and depend on the type of treatment, which in a given patient has been applied. (PNN 2013; 2(5): 223–227)